The Effect of Storage Time For Crispy Catfish Satay Raw Materials on Product Quality - Mahmudi, Nur; Mohammad Nurul Hidayatullah (Teknologi Hasil Pertanian, Fakultas Teknik, Universitas Annuqayah, 2024)
Crispy catfish satay is a diversification of processed products made from catfish. This research aims to determine the effect of storage time for crispy catfish satay raw materials on the physical characteristics of the product. This research uses a Completely Randomized Design (RAL) to process the data and data analysis is carried out using ANOVA and variance analysis. KruskalWallis with 3 treatments, namely storage time of 12 hours, 24 hours, and 36 hours. The results show that the results of the ANOVA variance analysis of the proximate content of the raw material for crispy catfish satay are water content (0.004 - 0.05), fat (0.001<0.05), protein (0.20<0.05), as well as carbohydrates, namely (0.18<0.05), so it can be stated that Ho is rejected. This means that there is a significant difference or influence between the independent variable and the dependent variable. The results of data processing for the physical characteristics test using the Kruskal-Wallis analysis method show that the three treatments storage time indicates that there is a significant average difference in aroma parameters (significance value 0.00), texture (significance value 0.00), while for appearance (significance value 0.00). So, with the 3 treatments, storage time has an influence or significant difference to product quality